TECHNOLOGY INTEGRATION IN A SECONDARY VOCATIONAL EFL CLASSROOM: PROCESS, CHALLENGES AND PERCEPTION - Selli Hernawati S, - (2019)
Technology has an important role in an educational program especially in the 21st century. The advancement of technology has given opportunities and a space for teachers to improve their teaching and learning process in the classroom. The teachers' roles are important in the process of Information and Communication Technology (ICT) integration because the use of ICT in the classrooms depends on the teachers' attitude to the concept of ICT. In other words, the success of technology integration in the classroom requires the teachers to have a positive belief so they are willing to improve their technical skill and knowledge. Thus, this research firstly examine the process of implementing technology integration in an EFL classroom by the English teachers at a vocational high school for agriculture. Second, this research identified the dominancy of challenges in implementing the ICT integration encountered by the teachers and students' perceptions towards of ICT integration in the teaching and learning process. In this study, descriptive qualitative approach was employed by conducting interview, questioner and classroom observation. As the result of the research indicated that in integrating the ICT in teaching and learning process, teachers and students have positive perception towards ICT integration therefore they are willing to improve their technological skill and knowledge. Second, they have to overcome some challenges in time allocation and technical problem in classroom. The results of this study indicated that teachers and students have positive perception towards ICT integration in thier teaching and learning process.; Teknologi memiliki peran penting dalam program pendidikan terutama di abad ke-21. Kemajuan teknologi telah memberi peluang dan ruang bagi guru untuk meningkatkan proses belajar mengajar di kelas. Peran para guru penting dalam proses integrasi Teknologi Informasi dan Komunikasi (TIK) karena penggunaan TIK di ruang kelas tergantung pada sikap guru terhadap konsep TIK. Dengan kata lain, keberhasilan integrasi teknologi di dalam kelas menuntut guru untuk memiliki keyakinan positif sehingga mereka bersedia untuk meningkatkan keterampilan dan pengetahuan teknis mereka. Dengan demikian, penelitian ini pertama-tama meneliti proses penerapan integrasi teknologi di ruang kelas EFL oleh para guru bahasa Inggris di sekolah menengah kejuruan untuk pertanian. Kedua, penelitian ini mengidentifikasi tantangan yang paling dominan mereka hadapi dalam mengimplementasikan integrasi TIK yang dihadapi oleh persepsi guru dan siswa terhadap integrasi TIK dalam proses belajar mengajar. Dalam penelitian ini, pendekatan deskriptif kualitatif digunakan dengan melakukan wawancara, kuesioner dan observasi kelas. Sebagai hasil penelitian menunjukkan bahwa dalam mengintegrasikan TIK dalam proses belajar mengajar, guru dan siswa memiliki persepsi positif terhadap integrasi TIK karena itu mereka bersedia untuk meningkatkan keterampilan dan pengetahuan teknologi mereka. Kedua, mereka harus mengatasi beberapa tantangan dalam alokasi waktu dan masalah teknis di kelas. Hasil penelitian ini menunjukkan bahwa guru dan siswa memiliki persepsi positif terhadap integrasi TIK dalam proses belajar mengajar mereka.